Payment Security: It's in the Cards. - MARGETTA, ROB (CQ Weekly, 2014)
The article discusses issues on payment security in credit and debit cards. Topics covered include the tokenization system, point-to-point encryption and replacement of the magnetic strips on cards with embedded microchips. Also mentioned are the PCI Security Standards Council, chip-and-PIN system and the zero-liability protection for credit card users.